The effects of rent control in Latin America: A century of regulations in Argentina - Alejandro D. Jacobo; Konstantin A. Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Following World War I, rent control became a standard policy response to the housing shortage and the resulting rent increases. Typically, economists blame it for creating inefficiencies in the housing market and beyond. We investigate whether rental market regulations (including rent control, protection of tenants from eviction, and housing rationing) had any effects in a middle-income Latin American economy, such as Argentina. To answer this question, we take advantage of a wide range of housing market indicators and restrictive rental regulation indices covering almost one century. Using a standard OLS model and MARS, a non-linear estimation technique, we find that rental market regulations have exerted a statistically significant negative impact on the growth rates of the real housing rents. However, they were only effective for short periods following both World Wars, when regulations were novel and particularly strong.
Keywords: C21; E31; R38; 330; Argentina; housing rents; rent control; rental market regulations